1990
DOI: 10.1093/jn/120.11.1283
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Isolated From Prickly Pear (Opuntia sp.) Modifies Low Density Lipoprotein Metabolism in Cholesterol-Fed Guinea Pigs

Abstract: The effect of prickly pear soluble fiber on low density lipoprotein (LDL) metabolism was investigated by feeding male guinea pigs either a nonpurified diet containing 0.25% cholesterol (HC diet) or the HC diet + 1% prickly pear pectin (HC-P diet). Plasma cholesterol levels were significantly decreased by the HC-P diet, with a 33% decrease in LDL levels (p less than 0.02) and an increase in LDL density. Hepatic free and esterified cholesterol levels were reduced 40 and 85%, respectively (p less than 0.002), by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…In a series of studies with Guinea pigs, Fernµndez et al [173 -175] demonstrated that the reduction of blood lipids triggered by isolated pectin from Opuntia was due to the enhanced binding of bile acid. It was concluded that through reduced bile absorption in the colon the enterohepatic circle was disrupted [173,174]. In a followup study, the same authors presented evidence that the lowdensity lipoprotein (LDL)-catabolism was considered to be more important than the modulation and de novo synthesis in the liver [175].…”
Section: Anti-hyperlipidemic Propertiesmentioning
confidence: 99%
“…In a series of studies with Guinea pigs, Fernµndez et al [173 -175] demonstrated that the reduction of blood lipids triggered by isolated pectin from Opuntia was due to the enhanced binding of bile acid. It was concluded that through reduced bile absorption in the colon the enterohepatic circle was disrupted [173,174]. In a followup study, the same authors presented evidence that the lowdensity lipoprotein (LDL)-catabolism was considered to be more important than the modulation and de novo synthesis in the liver [175].…”
Section: Anti-hyperlipidemic Propertiesmentioning
confidence: 99%
“…The effect of the prickly pear over the metabolism of the low-density lipoproteins has been studied by FernaH ndez et al (1990), suggesting, through its results, that the extract of prickly pear would act in a similar way to that of other compounds used to decrease cholesterol levels.…”
Section: Medical Usesmentioning
confidence: 99%
“…In the present study, we examined the antiviral activity of the cactus Opuntia ficus indica, and attempted to extract, isolate and identify the active compound(s). This plant, which grows in harsh climatic conditions (heat and dryness), was described as exhibiting several medicinal virtues including anti-diabetic [2,3], anti-cholesterol [4,5], anti-inflammatory [6], antioxidant [7], and anti-tumor [8] properties. However, reports on the antiviral activity of this cactus are limited to one publication [9].…”
Section: Introductionmentioning
confidence: 99%